On the h-manifolds for impulsive conformable neural networks with reaction–diffusion terms: Practical stability analysis - Martynyuk, Anatoliy; Stamov, Gani; Stamova, Ivanka (Nonlinear Analysis: Modelling and Control, 2025)
In this paper, we consider a new class of conformable impulsive reaction–diffusion neural networks. The stable behavior of h-manifolds with respect to the model is investigated, and sufficient conditions are proposed by constructing suitable Lyapunov-like functions. Our results are new and contribute to the development of the theory of impulsive conformable models. Examples are also presented to illustrate the proposed criteria.